The Success Rate of ERCP for Identification and Stenting in Obstructive Jaundice in Cipto Mangunkusumo Hospital October 2004-July 2007 - Simon Salim; Daniel Gunawan; Ilham Ahmadi; Marcellus Simadibrata; Achmad Fauzi; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2008)
Background: Obstructive jaundice can be caused by malignant or benign origin. The treatment for these situations includes drainage by biliary stenting. The aim of this study was to evaluate the success rate of Endoscopic Retrograde Cholangiopancreatography (ERCP) in evaluating malignant obstructive jaundice and the success rate of plastic stent placement. Method: We conducted a retrospective study based on data of ERCP in Cipto Mangunkusumo hospital from October 2004 until July 2007. Results: We evaluated 100 patients who had undergone ERCP examination, 92 (92%) of them had clinical diagnosis of obstructive jaundice (direct bilirubin indirect bilirubin). Those with obstructive jaundice were found to have no malignancy in 47 (51.1%) patients, with malignancy in 28 (30.4%) patients, and 17 (18.5%) of them would have further diagnostic evaluation. We had conducted a descriptive study in 36 patients who had tried to have plastic stent placement. Nineteen (52.8%) patients succeed in plastic stent placement; whereas 17 (47.2%) patients had failed. Further evaluation showed that age and sex did not affect stent successfulness, and malignancy was showed to be a factor for stent failure (malignancy: 16 fail and 6 successes (27.3%) vs. non malignancy: 1 fail and 13 successes (92.85%). Conclusion: Cipto Mangunkusumo hospital has acceptable success rate for diagnostic ERCP in obstructive jaundice patients. However, it is relatively lower than other studies, which might be caused by late referral and different standard instruments that were used. Keywords: obstructive jaundice, malignancy, ERCP, stent placement